2021
DOI: 10.21608/jpps.2021.222807
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability Variation of some White Maize Inbred Lines via Line X Tester Analysis under Ismailia and Mallawy Locations

Abstract: Combining ability analysis was conducted using Line x tester analysis involves twelve new white inbred lines of maize were crossed two single crosses (S.C 128 and S.C 131) as testers during 2018 season. The resulted 24 hybrids with check hybrid T.W.C 324 were evaluated in two locations (Ismailia and Mallawy Research Station) during 2019 season. The combined analysis over the two locations showed highly significant due to crosses, inbred lines (L), testers (T) and line x tester interaction (L x T) for grain yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Grain yield as the most important trait of selection programs, exhibited a significant association with non-additive gene action which suggested that specific combining ability (SCA) remark a good predictor for grain yield (Kamara et al, 2021 andEmam andMohamed, 2021). The low GCA to SCA variance ratio revealed the preponderance of non-additive gene action in the inheritance of grain yield (Kaur et al, 2010 andDinesh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Grain yield as the most important trait of selection programs, exhibited a significant association with non-additive gene action which suggested that specific combining ability (SCA) remark a good predictor for grain yield (Kamara et al, 2021 andEmam andMohamed, 2021). The low GCA to SCA variance ratio revealed the preponderance of non-additive gene action in the inheritance of grain yield (Kaur et al, 2010 andDinesh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%